Effects of operational assessment of the 4:4 and 4:4/6:6 watch systems on sleepiness, fatigue, and stress responses during patrolling on a navy missile patrol boat - Myllylä Mikko; Kyröläinen Heikki; Ojanen Tommi; Ruohola Juha-Petri; Heinonen Olli J; Vahlberg Tero; Parkkola Kai I (TAYLOR & FRANCIS INC, 2022)
The operation of naval vessels involves watchkeeping 24 h per day, which is globally carried out by a variety of different watch systems. In this study, the rotating 4:4 and fixed 4:4/6:6 two-section watch systems were compared in terms of sleepiness, fatigue, and stress responses. The data collection took place on a Finnish Defence Forces' (FDF) Navy missile patrol boat with 15 crew members serving as study participants. The data collection periods lasted two separate weeks (7 days, 6 nights) with the different watch systems. The subjective sleepiness of the participants was assessed before and after every watch using the Karolinska Sleepiness Scale (KSS). Stress responses were assessed daily by the recorded levels of salivary alpha-amylase (sAA), cortisol (sCor), immunoglobulin A (sIgA), and dehydroepiandrosterone (sDHEA). The participants' sustained attention, inhibitory control, and working memory were assessed daily by cognitive tests (SART, N-Back). The heart rate variability (HRV) during an orthostatic test was used as an additional daily marker to assess the amount of psychological stress of the participants. In this study, the difference regarding sleepiness and fatigue between the study weeks was most visible in the subjective KSS, which clearly favored the 4:4/6:6 system. The results of sAA and sIgA also suggested that the subjects were psychologically less stressed during the study week with the 4:4/6:6 watch system. Cognitive test results (SART, N-Back) indicated that there were overall no significant differences in the subjects' sustained attention, inhibitory control, or working memory during the study weeks or between the study weeks. The results of the HRV data during the daily orthostatic tests were inconclusive but there was some indication that the subjects were less stressed during the study week with the 4:4/6:6 watch system. In conclusion, the present study indicates that in navy surface operations: working with the fixed 4:4/6:6 watch system causes less sleepiness, fatigue, and psychological stress than working with the rotating 4:4 watch system. The study result is well in line with previous research regarding watch systems.